2021
DOI: 10.47276/lr.92.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Pure neural leprosy—mind the diagnosis

Abstract: Introduction: Pure Neural Leprosy (PNL) is a known clinical diagnosis of leprosy. There is great epidemiological variability in the diagnosis and there appears to be no consensus about its definition and classification. Given the reported prevalence it is for operational reasons important that there is consensus about its definition, classification and treatment. Method: The TENLEP (Treatment of early Neuropathy in LEProsy) database was used to analyze patients that were enrolled with a diagnosis of PNL to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…This paper reports on four young adults diagnosed with Hirayama Disease, a relatively rare neurological condition in endemic leprosy countries that could be confused with neural leprosy. [2][3][4]25,26 The clinical features of this disease are very typical. When there is adequate knowledge of the nerve involvement pattern in leprosy, including possible findings on nerve palpation, the condition should not be confused with leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reports on four young adults diagnosed with Hirayama Disease, a relatively rare neurological condition in endemic leprosy countries that could be confused with neural leprosy. [2][3][4]25,26 The clinical features of this disease are very typical. When there is adequate knowledge of the nerve involvement pattern in leprosy, including possible findings on nerve palpation, the condition should not be confused with leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article Brandsma et al reported 76 (8.8%) patients with Pure Neural Leprosy (PNL) in a cohort of 868 leprosy patients, while in a second cohort, the figure was 7.5% (N 28/372). 2 Correspondence to: Wim Brandsma (e-mail: jwbrandsma@gmail.com) Kumar reported 4.2% in 1542 patients, and in a recent review article Kumar reported a range of 4-8% in India. 3,4 Van Brakel reported 8.7% of patients with PNL in a cohort of 703 newly diagnosed patients in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually distal and symmetrical with proprioception, light touch, temperature, and pain sensory abnormalities without muscle weakness [ 17 , 19 , 21 ]. Tendon reflexes can be lost, reduced, or preserved, and electroneurography may show both demyelinating and axonal involvement or may be normal, thus suggesting the involvement of small fibers [ 17 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentations are mononeuropathy (79%) and multiple mononeuropathy (10.5%) [ 17 , 18 , 19 ]. A polyneuropathic form (P-PNL) is rarely reported in the literature, and diagnosis is often missed, especially in Western countries, where leprosy is not an endemic disease [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Sir,We read with interest the article by Brandsma et al entitled 'Pure neural leprosy-mind the diagnosis'. 1 The authors describe the demographics, prevalence, and nerve involvement in pure neural leprosy (PNL) from a large cohort of patients recruited originally in the TENLEP study. 2 The study has confirmed once again the existence of this subset of leprosy (PNL).
…”
mentioning
confidence: 99%